Case report and a brief review: Analysis and challenges of prenatal imaging phenotypes and genotypes in Joubert syndrome - Huang, Ling-Xi; Lu, Xian-Gui; Liu, Jiao-Xiang; Xu, Ling; Shang, Ning; Guo, Li; OuYang, Yan-Chun (Frontiers in Genetics, 2022)
Prenatal imaging phenotypes and genotypes were analyzed in 13 cases prenatally diagnosed with Joubert syndrome (JS), all of which underwent magnetic resonance imaging (MRI), ultrasound, and genetic testing. Prenatal MRI diagnosed 10 cases as JS with a typical molar tooth sign (MTS), while prenatal ultrasound diagnosed or suspiciously diagnosed 11 cases as JS with typical or mild MTS in 10 cases. Mutations in JS-related genes and other prenatal JS imaging phenotypes were identified in 10 cases, including OFD1 in two cases [cerebellar vermis (CV) absence, posterior fossa dilation, ventriculomegaly, polydactyly, malformations of cortical development (MCD), and persistent left superior vena cava], TMEM67 in two cases (CV absence, polydactyly, hyperechoic kidneys or polycystic kidneys, posterior fossa dilation, and ventriculomegaly), CC2D2A in two cases (CV absence, polydactyly, MCD, agenesis of the corpus callosum, encephalocele and hydrocephalus, ventriculomegaly, and posterior fossa dilation), RPGRIP1L in one case (CV absence), TCTN3 in one case (CV absence, polydactyly, MCD, and posterior fossa dilation), CEP290 in one case (CV absence and polycystic kidney), and NPHP1 in one case (CV absence). The prenatal diagnosis of JS presents a number of challenges, including the variants of unknown significance, the lack of functional assessment in prenatal imaging, unclear phenotype–genotype relationships in prenatal evaluation, and the incorrect identification of the JS hallmark, the MTS, in prenatal imaging, especially on ultrasound. Although combined MRI, ultrasound, and exome sequencing could help improve the prenatal diagnosis of JS, there still exist significant challenges.